2017
DOI: 10.1007/s10120-017-0772-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of endoscopic submucosal dissection versus surgery in early gastric cancer meeting expanded indication including undifferentiated-type tumors: a criteria-based analysis

Abstract: ESD may be an alternative treatment option to surgery for EGCs meeting expanded indications, including undifferentiated-type tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…112,113 However, retrospective studies reported a low incidence of extragastric metastasis during follow-up and high five-year survival rates of 95.0%-98.6% among patients who underwent endoscopic resection for undifferentiated type adenocarcinoma with mucosal invasion, no ulcer and ≤2 cm in size. 100,[114][115][116][117][118] Studies also reported no significant difference in long-term outcomes between endoscopic resection and surgical resection for the aforementioned lesions. 95,100,103,118 Thus, endoscopic resection may be recommended for undifferentiated type gastric adenocarcinoma with mucosal invasion, no ulcer and ≤2 cm in size.…”
Section: Statement G5mentioning
confidence: 99%
See 1 more Smart Citation
“…112,113 However, retrospective studies reported a low incidence of extragastric metastasis during follow-up and high five-year survival rates of 95.0%-98.6% among patients who underwent endoscopic resection for undifferentiated type adenocarcinoma with mucosal invasion, no ulcer and ≤2 cm in size. 100,[114][115][116][117][118] Studies also reported no significant difference in long-term outcomes between endoscopic resection and surgical resection for the aforementioned lesions. 95,100,103,118 Thus, endoscopic resection may be recommended for undifferentiated type gastric adenocarcinoma with mucosal invasion, no ulcer and ≤2 cm in size.…”
Section: Statement G5mentioning
confidence: 99%
“…[99][100][101] Additionally, studies reported no significant difference between the five-year survival rate of surgical resection and endoscopic resection (92.0%-97.2% vs. 93.3%-96.4%), indicating that endoscopic resection is considered curative for the aforementioned lesions with no requirement of further treatment. 95,100,[102][103][104][105][106][107][108][109] Surgical resection is the standard treatment for clinically suspected submucosal invasive gastric cancer in preoperative evaluation. However, studies analyzing pathologic results of patients who underwent gastrectomy due to preoperatively suspected submucosal invasion reported that 28.8%-43.0% of these lesions could have been treated with endoscopic resection.…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 99%
“…In fact, the former did have higher risk of local recurrence and metachronous lesions than those undergoing surgery . However, results of studies showed that ESD had a similar 5‐year OS and 5‐year CSS to surgery irrespective of the absolute or expanded indication for endoscopic resection, location (stomach or esophagogastric junction), or age of the patients …”
Section: Surveillance Strategy For Egcmentioning
confidence: 99%
“…Curative endoscopic surgery alone was not rarely reported to cure localized primary tumor, especially among early gastric cancer, colorectal neoplasia, and glottic cancer, as it could achieve radical resection of the localized primary tumor in early stage cancer without regional lymph nodes metastasis. Nasopharyngeal carcinoma (NPC) is common head and neck cancer in China and Southeast Asia, with a reported annual incidence of 50 per 100 000 population .…”
Section: Introductionmentioning
confidence: 99%